2013
DOI: 10.1007/s00426-013-0493-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduced habituation to angry faces: increased attentional capture as to override inhibition of return

Abstract: The aim of this paper was to study whether real angry faces do capture attention to the extent of overcoming the inhibition of return (IOR) effect and whether the anxiety level of participants modulates this effect by stressing biases toward threatening stimuli. With this purpose, participants categorized the emotional valence of face targets in a standard spatial cueing procedure suitable to measure IOR. In Experiment 1, participants were selected according to their high vs. low-trait anxiety, whereas in Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 67 publications
3
21
0
Order By: Relevance
“…Our findings are supported by previous studies that used a cueing paradigm to examine what type of stimulus could override the IOR effect (Baijal and Srinivasan 2011;Dai and Feng 2009;Fox et al 2002;Pérez-Dueñas et al 2014;Verkuil et al 2009). They found that some emotional stimuli could modulate the IOR effect.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings are supported by previous studies that used a cueing paradigm to examine what type of stimulus could override the IOR effect (Baijal and Srinivasan 2011;Dai and Feng 2009;Fox et al 2002;Pérez-Dueñas et al 2014;Verkuil et al 2009). They found that some emotional stimuli could modulate the IOR effect.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, using schematic facial expressions as target stimuli in a detection task, Baijal and Srinivasan (2011) found that IOR was reduced for sad faces compared to happy ones. Pérez-Dueñas et al (2014) observed an elimination of the IOR effect when the target was a biologically relevant angry face. These studies examined the influence of emotion on the IOR effect in an explicit way by using emotional stimuli as targets, and the results were consistent with the evolutionary perspective that more attention is captured by emotionally negative stimuli.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Allocation of attentional resources is driven by relative salience of stimuli encountered in the environment, where high salience can be generated by the relative configuration of low-level features such as color, orientation and size in the scene (Itti and Koch, 2001; Soltani and Koch, 2010) or by an interaction between sensory features and reward (Markowitz et al, 2011; Theeuwes and Belopolsky, 2012; Khorsand et al, 2015). Similarly, valence of the face cue (e.g., faces with expression of emotion such as fear, happy, neutral, or sad or one’s own face; Pourtois et al, 2013; Pérez-Duenas et al, 2014; Porciello et al, 2014) has been shown to modulate the magnitude of attentional capture. Thus, spatial reallocation of attention in response to gaze shifts in familiar faces could be facilitated by faster processing of the gaze cue or slowed by the social saliency of familiar faces.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still uncertain that how biological stimuli can modulate IOR effect. Some studies found emotion stimuli can modulate the IOR effect for clinical populations (Fox et al, 2001; Pérez-Dueñas et al, 2014). Other literature measuring the IOR effect of emotional cues or targets, suggests that IOR is a “blindness mechanism” that is not affected by the occurrence of biologically relevant cues and targets (Taylor and Therrien, 2005; Stoyanova et al, 2007; Lange et al, 2008).…”
Section: Introductionmentioning
confidence: 99%